A porous structure synergistic desulfurization and denitration catalyst, a preparation method and application thereof

CN118616035BActive Publication Date: 2026-10-09NANJING TECH UNIV +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410672840.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2026-10-09
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

但是在低温条件下,NH3易与SO2结合形成(NH4)2SO4附着于催化剂表面,造成催化活性的急剧降低,催化剂寿命急剧减少

Benefits of technology

[0028] This invention discloses a method for preparing and applying a porous synergistic desulfurization and denitrification catalyst. The catalyst uses porous TiO2 as a support and Ce-W-Pr-Co multimetal oxide as the active component, prepared via a one-step molding method. The key to this method lies in the synthesis of porous TiO2, using surface-modified microplastics as a template to synthesize the TiO2. 4+A porous structure is obtained by coating the template surface and calcining. This porous structure increases the specific surface area, improves the contact area between the catalyst and reactants, and the channel effect effectively enhances the catalytic efficiency. Within the temperature range of 350–420℃, this catalyst exhibits high synergistic removal efficiency for NO and SO2, with denitrification efficiency maintained above 90% and desulfurization efficiency above 80%. This catalyst converts SO2 into elemental sulfur, enabling waste resource recycling and possessing high economic value and broad market application prospects. It also provides a potential solution to the current serious problem of white pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118616035B_ABST
    Figure CN118616035B_ABST
Patent Text Reader

Abstract

The application discloses a porous structure synergic desulfurization and denitration catalyst and a preparation method and application thereof, and relates to the technical field of catalysts, in particular to a porous structure TiO2 as a carrier and Ce-W-Pr-Co multi-metal oxides as active components. The key of the scheme lies in the preparation of the porous structure TiO2, in which microplastics are used as templates, a surface modifier is added, and the surface hydrophilicity is improved by using a microwave-assisted method, then the microplastic templates are coated with titanium salt precursors, and the porous structure TiO2 is obtained by calcination. Then, the active component precursors are mixed with the porous structure TiO2, and the mixture is shaped and calcined to obtain the finished catalyst. The catalyst is rich in pores, has a high specific surface area, can synergically remove NO and SO2 in flue gas, has high catalytic activity and is easy to regenerate, can convert SO2 into elemental sulfur to realize waste regeneration, and has the advantages of simple process, easily available raw materials and the like, and has high economic value and wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention discloses a method for preparing and applying a porous structure synergistic desulfurization and denitrification catalyst, belonging to the field of air pollution control. Background Technology

[0002] NO and SO2 are the largest air pollutants emitted in large-scale industrial production, and their treatment has been extensively researched and applied. Selective oxidation-reduction (NH3-SCR) is currently the most mainstream denitrification technology, where NO and NH3 react to produce H2O and N2 under the action of a catalyst. Patent CN112958063B discloses a denitrification catalyst in which micropores are etched into the surface of porous titanium metal and an oxide film is formed by anodic oxidation. Finally, active components are loaded to form a three-dimensional porous MnCeOx / TiO2 / foamed Ti denitrification catalyst. The three-dimensional porous structure of this catalyst increases its specific surface area, giving it excellent denitrification activity and making it suitable for low-temperature denitrification. Another example is the Ru-MnOx / graphene denitrification catalyst disclosed in patent CN111569873B, which possesses a nanoflower-like structure and uniform Ru distribution on the support surface, resulting in excellent conversion rate and selectivity.

[0003] Currently, there are three technical solutions for SO2 removal: wet methods, dry methods, and combined wet and dry methods. Among them, producing sulfur from SO2 using a catalyst not only solves the air pollution problem but is also an excellent solution for turning waste into treasure and recycling resources. The journal article "Research Progress on Sulfur Dioxide to Sulfur Production Technology" introduces the advantages and disadvantages of common technologies. Because CO is widely present in flue gas and various reaction gases, and because the reaction temperature is low and the elemental sulfur recovery rate is high, the CO reduction method is considered one of the most promising technologies.

[0004] Currently, integrated desulfurization and denitrification processes have become a research hotspot for flue gas pollution control in various countries. Patent CN101816948B discloses a catalytic desulfurization and denitrification catalyst and its application. This scheme uses phosphorus-modified γ-Al2O3 as a support and Ni and Co as active components, prepared by an impregnation method. It exhibits excellent conversion rate and selectivity, and can convert SO2 into elemental S, enabling waste reuse. However, this scheme uses H2 as a reducing gas, increasing its risk and limiting its application areas. Another example is the desulfurization and denitrification catalyst disclosed in patent CN105921181B, prepared from iron bauxite, honeycomb activated carbon, neutral clay, starch, samarium oxide, platinum, sodium lauryl sulfate, polypropylene glycol, dicumyl peroxide, and carbon fiber. It exhibits good catalytic efficiency at low temperature and low space velocity. However, the process is complex, and the use of precious metals as active components results in high costs, making industrialization difficult. Patent CN109603807A discloses a desulfurization and denitrification catalyst that uses modified activated carbon and mesoporous TiO2 as a composite support, with Ce-NbOx bimetallic active components loaded to form a composite denitrification catalyst. This catalyst can achieve a denitrification efficiency of over 90% and a high desulfurization value of 115 mg / g within a temperature range of 80-200℃. However, at low temperatures, NH3 readily combines with SO2 to form (NH4)2SO4, which adheres to the catalyst surface, causing a sharp decrease in catalytic activity and a drastic reduction in catalyst lifetime. Therefore, the development of a catalyst with high desulfurization and denitrification efficiency and a long lifespan is urgently needed. Summary of the Invention

[0005] The purpose of this invention is to address the current situation of severe air pollution and the lack of catalysts that can synergistically remove NO and SO2 by providing a method for preparing and applying a porous structure synergistic desulfurization and denitrification catalyst.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] A porous structure synergistic desulfurization and denitrification catalyst is provided. The catalyst uses porous TiO2 as a support and Ce-W-Pr-Co polymetallic oxide as the active component. Based on the mass of the support, the mass percentage of the active component is 12-18%, and the mass ratio of CeO2:WO3:Pr2O3:CoO is (40-55):(5-10):(10-20):(20-30).

[0008] A method for preparing the above-mentioned catalyst, the method comprising the following steps:

[0009] (1) The plastic powder was ground and screened to a fine powder of 400-600 mesh and dispersed in deionized water. A surface modifier was added to the suspension and stirred for 1 hour. Then it was transferred to a microwave chemical reactor for microwave-assisted treatment.

[0010] (2) Add titanium source to the suspension in step (1), stir evenly, filter, wash and dry to obtain powder solid;

[0011] (3) Transfer the powder obtained in step (2) to a muffle furnace for calcination;

[0012] (4) The active component precursor is dissolved in deionized water to prepare a solution. At the same time, the powder obtained in step (3) is mixed evenly with the binder. The active component precursor solution is added to the mixed powder and stirred to make mud. After aging, it is transferred to an oven to dry thoroughly to form a catalyst ligand.

[0013] (5) The catalyst preform obtained in step (4) is transferred to a muffle furnace and calcined to obtain the finished catalyst.

[0014] In the above method: the plastic mentioned in step (1) is one of polyethylene plastic, polypropylene plastic, polystyrene plastic or polyethylene terephthalate plastic, and the particle size of the plastic after grinding is 400 to 600 mesh.

[0015] The mass ratio of the plastic powder to deionized water in step (1) is 1:(50-100);

[0016] The surface modifier obtained in step (1) is sodium dodecylbenzenesulfonate (SDS); the mass ratio of the surface modifier added to the plastic powder is (15-20):100.

[0017] In the above method: the microwave-assisted treatment in step (1) using a microwave chemical reactor has a power of 500-800W, a controlled temperature of 70-90℃, and a treatment time of 5-10min.

[0018] In the above method: the titanium source in step (2) is titanium sulfate, and the mass ratio of titanium sulfate to plastic powder in step (1) is (4-6):10; the stirring time is 6-12h, the stirring temperature is 25-40℃, and the drying temperature is 60-80℃.

[0019] In the above method: the roasting temperature in step (3) is 400-450℃, the roasting time is 4-8h, and the roasting environment is air or oxygen atmosphere.

[0020] In the above method: the precursor of the active component in step (4) is cerium nitrate for CeO2, ammonium metatungstate for WO3, praseodymium nitrate for Pr2O3, and cobalt nitrate for CoO;

[0021] The binder in step (4) is one of polyvinyl alcohol (PVA) and polyethylene oxide (PEO); the mass of the binder added is 2 to 5% of the mass of the powder obtained in step (3).

[0022] In the above method: the aging time in step (4) is 24-48 hours, and the drying temperature is 80-100℃;

[0023] The roasting temperature in step (5) is 400-450℃, the roasting time is 4-6h, and the roasting environment is air or oxygen atmosphere.

[0024] The application of the catalyst in desulfurization and denitrification in the technical solution of this invention.

[0025] Preferably, the desulfurization and denitrification temperature range is 350–420℃, and the CO content in the flue gas is 3–8%.

[0026] This catalyst is prepared using porous TiO2 as a support and Ce-W-Pr-Co polymetallic oxide as the active component via a one-step molding method. This scheme uses plastic powder as a hard template to prepare porous TiO2. Since the plastic surface is hydrophobic, it is modified with a surface modifier, and microwave-assisted modification is used to bring the plastic to a critical state, reducing its surface tension and promoting surface modification. The surface-modified plastic surface is rich in hydroxyl and sodium sulfonate groups. After introducing titanium salt, Ti4+ is adsorbed and coated onto the plastic surface, and calcination yields porous TiO2. The active component precursor solution is prepared, mixed with porous TiO2 and a binder, then slurry-refined, aged, dried, and calcined to obtain the finished catalyst. In the selection of active component elements, CeO2 not only serves as the main active element for denitrification, but also converts some stable SO2 into unstable SO3, promoting the desulfurization reaction; WO3 can enter the CeO2 lattice, causing lattice distortion and inhibiting the expansion or contraction of the CeO2 lattice, thereby improving the catalyst's resistance to sintering; Pr2O3 and CoO are the main active components for desulfurization, and their excellent redox capabilities convert SO2 / SO3 adsorbed on the surface into elemental sulfur, while also possessing certain denitrification activity.

[0027] Beneficial effects:

[0028] This invention discloses a method for preparing and applying a porous synergistic desulfurization and denitrification catalyst. The catalyst uses porous TiO2 as a support and Ce-W-Pr-Co multimetal oxide as the active component, prepared via a one-step molding method. The key to this method lies in the synthesis of porous TiO2, using surface-modified microplastics as a template to synthesize the TiO2. 4+A porous structure is obtained by coating the template surface and calcining. This porous structure increases the specific surface area, improves the contact area between the catalyst and reactants, and the channel effect effectively enhances the catalytic efficiency. Within the temperature range of 350–420℃, this catalyst exhibits high synergistic removal efficiency for NO and SO2, with denitrification efficiency maintained above 90% and desulfurization efficiency above 80%. This catalyst converts SO2 into elemental sulfur, enabling waste resource recycling and possessing high economic value and broad market application prospects. It also provides a potential solution to the current serious problem of white pollution. Attached Figure Description

[0029] Figure 1 Example 2: FE-SEM image;

[0030] Figure 2 Detailed implementation method NO removal efficiency diagram;

[0031] Figure 3 Detailed implementation method, SO2 removal efficiency diagram. Detailed Implementation

[0032] The following examples further illustrate the preparation method and application of the porous structure synergistic desulfurization and denitrification catalyst of the present invention. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operating procedures are provided. However, the scope of protection of the present invention is not limited to the following examples.

[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods in the art, and the experimental apparatus and materials are commercially available unless otherwise specified. The microwave chemical reactor is a BILON-W-1000 microwave chemical reactor provided by Shanghai Bilang Instrument Manufacturing Co., Ltd.

[0034] Catalyst performance testing: The catalyst was crushed, and 2 ml of 20-40 mesh particles were screened and transferred to the center of the quartz reactor. The catalyst was secured on both sides with quartz wool. Simulated flue gas (NO 1000ppm, NH3 1000ppm, SO2 1000ppm, CO 5%, O2 10%, N2 as carrier gas, space velocity 20000h) was introduced into one end of the quartz reactor. -1 The reactor temperature was controlled within the range of 350 to 420°C, and the temperature was maintained at 10°C for 30 minutes. The composition of the exhaust gas was then measured.

[0035] Example 1

[0036] Polyethylene plastic granules were ground, and 50g of the 400-600 mesh fine powder was dispersed in 2500g of deionized water to form a suspension. Then, 9g of sodium dodecylbenzenesulfonate (SDS) was weighed and dissolved in the suspension. The mixture was stirred for 1 hour, then transferred to a microwave chemical reactor and treated at 500W and 90℃ for 5 minutes. Next, 20g of Ti(SO4)2 was weighed and dissolved in the suspension. After stirring continuously at 40℃ for 8 hours, the mixture was filtered, washed, and dried at 60℃ to obtain Ti ion-coated plastic powder. The powder was transferred to a muffle furnace and calcined at 420℃ for 4 hours, during which air was continuously introduced into the furnace at 20ml / min, yielding 6.35g of porous TiO2. 0.9106 g Ce(NO3)3·6H2O, 0.0441 g ammonium metatungstate hydrate, 0.4232 g Pr(NO3)3·6H2O, and 0.7788 g Co(NO3)2·6H2O were dissolved in 6.35 g deionized water to form an active solution. Porous TiO2 powder was mixed evenly with 0.254 g polyvinyl alcohol (PVA). The active solution was then added to the mixed powder, mixed thoroughly, wrapped in plastic wrap, and aged for 36 h before being thoroughly dried at 100 °C. Finally, it was transferred to a muffle furnace and calcined at 450 °C for 4 h, during which oxygen was continuously introduced at a rate of 20 ml / min to obtain the finished catalyst.

[0037] Example 2

[0038] Polypropylene plastic granules were ground, and 50g of the 400-600 mesh fine powder was dispersed in 3750g of deionized water to form a suspension. Then, 9g of sodium dodecylbenzenesulfonate (SDS) was weighed and dissolved in the suspension. The mixture was stirred for 1 hour, then transferred to a microwave chemical reactor and treated at 700W and 70℃ for 8 minutes. Next, 25g of Ti(SO4)2 was weighed and dissolved in the suspension. After stirring continuously at 30℃ for 12 hours, the mixture was filtered, washed, and dried at 70℃ to obtain Ti ion-coated plastic powder. The powder was transferred to a muffle furnace and calcined at 400℃ for 6 hours, during which oxygen was continuously introduced into the furnace at 20ml / min, yielding 7.86g of porous TiO2. 1.5291g Ce(NO3)3·6H2O, 0.1333g ammonium metatungstate hydrate, 0.5995g Pr(NO3)3·6H2O, and 1.1770g Co(NO3)2·6H2O were dissolved in 8.646g deionized water to form an active solution. Porous TiO2 powder was mixed evenly with 0.393g polyethylene oxide (PEO). The active solution was then added to the mixed powder, mixed thoroughly, wrapped in plastic wrap, and aged for 24 hours before being thoroughly dried at 80℃. Finally, it was transferred to a muffle furnace and calcined at 420℃ for 6 hours, during which air was continuously introduced at 20ml / min to obtain the finished catalyst.

[0039] Example 3

[0040] Polystyrene plastic granules were ground, and 50g of 400-600 mesh fine powder was dispersed in 5000g of deionized water to form a suspension. Then, 7.5g of sodium dodecylbenzenesulfonate (SDS) was weighed and dissolved in the suspension. The mixture was stirred for 1 hour, then transferred to a microwave chemical reactor and treated at 800W and 80℃ for 6 minutes. Next, 20g of Ti(SO4)2 was weighed and dissolved in the suspension. The mixture was stirred continuously at 25℃ for 6 hours, then filtered, washed, and dried at 80℃ to obtain Ti ion-coated plastic powder. The powder was transferred to a muffle furnace and calcined at 450℃ for 8 hours, during which air was continuously introduced into the furnace at 20ml / min, yielding 6.61g of porous TiO2. 1.5724 g Ce(NO3)3·6H2O, 0.1247 g ammonium metatungstate hydrate, 0.2989 g Pr(NO3)3·6H2O, and 1.3203 g Co(NO3)2·6H2O were dissolved in 7.932 g deionized water to form an active solution. Porous TiO2 powder was mixed evenly with 0.198 g polyethylene oxide (PEO). The active solution was then added to the mixed powder, mixed thoroughly, wrapped in plastic wrap, and aged for 48 h before being thoroughly dried at 90 °C. Finally, it was transferred to a muffle furnace and calcined at 450 °C for 6 h, during which air was continuously introduced at 20 ml / min to obtain the finished catalyst.

[0041] Example 4

[0042] Polyethylene terephthalate (PET) plastic granules were ground, and 50g of the 400-600 mesh fine powder was dispersed in 2500g of deionized water to form a suspension. Then, 10g of sodium dodecylbenzenesulfonate (SDS) was weighed and dissolved in the suspension. The mixture was stirred for 1 hour, then transferred to a microwave chemical reactor and treated at 800W and 90℃ for 10 minutes. Next, 30g of Ti(SO4)2 was weighed and dissolved in the suspension. After stirring continuously at 30℃ for 8 hours, the mixture was filtered, washed, and dried at 80℃ to obtain Ti ion-coated plastic powder. The powder was transferred to a muffle furnace and calcined at 425℃ for 4 hours, during which oxygen was continuously introduced into the furnace at 20ml / min, yielding 9.67g of porous TiO2. 1.7606 g Ce(NO3)3·6H2O, 0.1075 g ammonium metatungstate hydrate, 0.3682 g Pr(NO3)3·6H2O, and 1.6262 g Co(NO3)2·6H2O were dissolved in 9.67 g deionized water to form an active solution. Porous TiO2 powder was mixed evenly with 0.387 g polyvinyl alcohol (PVA). The active solution was then added to the mixed powder, mixed thoroughly, wrapped in plastic wrap, and aged for 36 h before being thoroughly dried at 90 °C. Finally, it was transferred to a muffle furnace and calcined at 400 °C for 5 h, during which oxygen was continuously introduced at a rate of 20 ml / min to obtain the finished catalyst.

[0043] Comparative Example 1

[0044] Polypropylene plastic granules were ground, and 50g of the 400-600 mesh fine powder was dispersed in 3750g of deionized water to form a suspension. Then, 9g of sodium dodecylbenzenesulfonate (SDS) was weighed and dissolved in the suspension, and stirred for 1 hour. Next, 25g of Ti(SO4)2 was weighed and dissolved in the suspension, and stirred continuously at 30℃ for 12 hours. The mixture was then filtered, washed, and dried at 70℃ to obtain Ti ion-coated plastic powder. The powder was transferred to a muffle furnace and calcined at 400℃ for 6 hours, during which oxygen was continuously introduced into the furnace at 20ml / min, yielding 7.66g of porous TiO2. 1.4902 g Ce(NO3)3·6H2O, 0.1300 g ammonium metatungstate hydrate, 0.5843 g Pr(NO3)3·6H2O, and 1.1471 g Co(NO3)2·6H2O were dissolved in 8.426 g deionized water to form an active solution. Porous TiO2 powder was mixed evenly with 0.383 g polyethylene oxide (PEO). The active solution was then added to the mixed powder, mixed thoroughly, wrapped in plastic wrap, and aged for 24 h before being thoroughly dried at 80 °C. Finally, it was transferred to a muffle furnace and calcined at 420 °C for 6 h, during which air was continuously introduced at a rate of 20 ml / min to obtain the finished catalyst.

[0045] Comparative Results: With other conditions kept constant, compared to Example 2, Comparative Example 1 eliminated microwave-assisted treatment, resulting in the surface modifier sodium dodecylbenzenesulfonate not being fully grafted onto the plastic surface, leading to a decrease in TiO2 porosity and specific surface area. The denitrification performance was significantly lower than in Example 2.

[0046] Comparative Example 2

[0047] 1.5291g Ce(NO3)3·6H2O, 0.1333g ammonium metatungstate hydrate, 0.5995g Pr(NO3)3·6H2O, and 1.1770g Co(NO3)2·6H2O were dissolved in 8.646g deionized water to form an active solution. 7.86g titanium dioxide (provided by Chaocai Environmental New Materials Technology Co., Ltd.) was weighed and mixed evenly with 0.393g polyethylene oxide (PEO). The active solution was then added to the mixed powder, mixed thoroughly, wrapped with plastic wrap, aged for 24 hours, and then thoroughly dried at 80℃. Finally, it was transferred to a muffle furnace and calcined at 420℃ for 6 hours, during which air was continuously introduced at 20ml / min to obtain the finished catalyst.

[0048] Comparative results: Comparative Example 2 used commercially available titanium dioxide as a carrier and controlled the addition ratio of each active component to be the same as in Example 2. Due to the decrease in the specific surface area of ​​the carrier, the catalytic activity decreased significantly.

Claims

1. A porous structure synergistic desulfurization and denitrification catalyst, characterized in that: The catalyst uses porous TiO2 as a support and Ce-W-Pr-Co polymetallic oxide as the active component. Based on the mass of the support, the mass percentage of the active component is 12-18%, and the mass ratio of CeO2:WO3:Pr2O3:CoO is (40-55):(5-10):(10-20):(20-30). The preparation method of this catalyst includes the following steps: (1) The plastic powder was ground and screened to a fine powder of 400~600 mesh and dispersed in deionized water. A surface modifier was added to the suspension and stirred for 0.5~1h. Then it was transferred to a microwave chemical reactor for microwave-assisted treatment. The surface modifier was sodium dodecylbenzene sulfonate (SDS). (2) Add titanium source to the suspension in step (1), stir evenly, filter, wash and dry to obtain powder solid; (3) Transfer the powder obtained in step (2) to a muffle furnace for calcination; (4) The active component precursor is dissolved in deionized water to prepare a solution. At the same time, the powder obtained in step (3) is mixed evenly with the binder. The active component precursor solution is added to the mixed powder and stirred to make mud. After aging, it is transferred to an oven to dry thoroughly to form a catalyst ligand. (5) The catalyst preform obtained in step (4) is transferred to a muffle furnace and calcined to obtain the finished catalyst.

2. The porous structure synergistic desulfurization and denitrification catalyst according to claim 1, characterized in that: The plastic mentioned in step (1) is one of polyethylene plastic, polypropylene plastic, polystyrene plastic or polyethylene terephthalate plastic, and the particle size of the plastic after grinding is 400~600 mesh. The mass ratio of plastic powder to deionized water in step (1) is 1:(50~100); the mass ratio of surface modifier added to plastic powder is (15~20):

100.

3. The porous structure synergistic desulfurization and denitrification catalyst according to claim 1, characterized in that: In step (1), the microwave-assisted treatment using a microwave chemical reactor has a power of 500-800W, a controlled temperature of 70-90℃, and a treatment time of 5-10min.

4. The porous structure synergistic desulfurization and denitrification catalyst according to claim 1, characterized in that: The titanium source in step (2) is titanium sulfate, and the mass ratio of titanium sulfate to plastic powder in step (1) is (4~6):10; the stirring time is 6~12h, the stirring temperature is 25~40℃, and the drying temperature is 60~80℃.

5. The porous structure synergistic desulfurization and denitrification catalyst according to claim 1, characterized in that: The roasting temperature in step (3) is 400~450℃, the roasting time is 4~8h, and the roasting environment is air or oxygen atmosphere.

6. The porous structure synergistic desulfurization and denitrification catalyst according to claim 1, characterized in that: The precursors of the active components mentioned in step (4) are: cerium nitrate for CeO2, ammonium metatungstate for WO3, praseodymium nitrate for Pr2O3, and cobalt nitrate for CoO. The binder in step (4) is one of polyvinyl alcohol (PVA) and polyethylene oxide (PEO); the mass of the binder added is 2 to 5% of the mass of the powder obtained in step (3).

7. The porous structure synergistic desulfurization and denitrification catalyst according to claim 1, characterized in that: The aging time in step (4) is 24~48h, and the drying temperature is 80~100℃; The roasting temperature in step (5) is 400~450℃, the roasting time is 4~6h, and the roasting environment is air or oxygen atmosphere.

8. The application of the porous structure synergistic desulfurization and denitrification catalyst according to claim 1 in desulfurization and denitrification.

9. The application according to claim 8, characterized in that, The temperature range for desulfurization and denitrification is 350~420℃, and the CO content in the flue gas is 3~8%.

Citation Information

Patent Citations

  • Catalytic desulfurization and denitrification catalyst and application thereof

    CN101816948B

  • A high-quality desulfurization and denitrification catalyst, its preparation method and application

    CN105921181B

  • Modified activated carbon Ce-Nb / TiO2@AC low-temperature high-efficiency desulfurization and denitrification catalyst and preparation method thereof

    CN109603807A

  • A denitrification catalyst

    CN112958063B

  • Composition for desorbing sulfur and nitrogen oxide in fume

    CN101721911A